2009
DOI: 10.1016/j.jim.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Engineered cell surface expression of membrane immunoglobulin as a means to identify monoclonal antibody-secreting hybridomas

Abstract: Monoclonal antibodies (mAbs) have proven to be effective biological reagents in the form of therapeutic drugs and diagnostics for many pathologies, as well as valuable research tools. Existing methods for isolating mAb-producing hybridomas are tedious and time consuming. Herein we describe a novel system in which mAb-secreting hybridoma cells were induced to co-express significant amounts of the membrane form of the secreted immunoglobulin (Ig) on their surfaces and are efficiently recovered by fluorescent act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Antibody secreting hybridoma cell lines were isolated by fluorescent-activated cell sorting (FACS) based on expression of the membrane isovariant of that antibody in the B cell antigen receptor (BCR) complex on the cell surface using a proprietary process described previously [16]. Briefly, this process relies on fusing splenocytes with a myeloma (SP2ab) that has been genetically engineered to constitutively express the Iga and Igb (CD79a and CD79b) components of the BCR.…”
Section: Generation Of Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody secreting hybridoma cell lines were isolated by fluorescent-activated cell sorting (FACS) based on expression of the membrane isovariant of that antibody in the B cell antigen receptor (BCR) complex on the cell surface using a proprietary process described previously [16]. Briefly, this process relies on fusing splenocytes with a myeloma (SP2ab) that has been genetically engineered to constitutively express the Iga and Igb (CD79a and CD79b) components of the BCR.…”
Section: Generation Of Antibodiesmentioning
confidence: 99%
“…Hybridomas were removed from culture, washed, labeled with biotin-conjugated PMA fractions, and counterstained with streptavidin-conjugated r-phycoerythrin (BD Biosciences) and allophycocyaninconjugated goat anti-mouse Ig (Invitrogen). Sorting was done using a FACS AriaÔ Flow Cytometer (BD Biosciences) as described previously [16]. Cells positive for both Ig expression and PMA reactivity were deposited singly into 96-well culture plates containing Iscove's modified Dulbecco's media supplemented with 20% fetal bovine serum, hypoxanthine, and thymidine (Sigma-Aldrich).…”
Section: Generation Of Antibodiesmentioning
confidence: 99%
“…From these findings we conclude that our optimized immunofluorescence staining procedure is specific. Price et al, 2009 showed different amounts of cell surface IgG on transfected cells by immunofluorescence microscopy. However, microscopic images of antigen-specific antibodies on the surface of hybridoma cells have not been shown in the literature so far.…”
Section: Discussionmentioning
confidence: 97%
“…In another context genetically modified hybridoma cells were sorted antigen-specifically via a streptavidin/biotin system (Price et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2A). SP2/0 murine myeloma cells that express endogenous Igb 16 were transfected with vectors containing sequences encoding the individual constructs, and surface expression of SM03 binding moiety was examined by flow cytometry (Fig. 2B).…”
Section: Surrogate Target Cells Expressing Surface Hc5 For Monitoringmentioning
confidence: 99%